PEMBUATAN AKTA/SURAT KETERANGAN WARIS OLEH NOTARIS BAGI MASYARAKAT ADAT BALI - Sudradjat, Debiana Dewi (Faculty of Law, Parahyangan Catholic University, 2020)
The legal basis justifying the existence of notaries as public officials and a legal profession were Netherland-Indies laws. These colonial laws were, by virtue of Art. I Transitional Rules of the 1945 Constitution of the Republic of Indonesia (4th Amendment), taken over and considered to be still in force. Consequently, one of the public service offered by Notary publics, i.e., issuance of letter of inheritance or written affidavit stating which family members of the deceased may by law be regarded as heir-successor, has not been made available to Balinese adat communities. This service can only be enjoyed by those individuals who submit themselves to the (colonial) Civil Code. The article explores, using a juridical empirical approach, the possibility to extent the above public notary’s service to Balinese adat (traditional) communities.